Puerarin: A Potential Therapeutic for Colon Adenocarcinoma (COAD) Patients Suffering From SARS-CoV-2 Infection - Liang, Weizheng; Li, Xiushen; Yao, Yue; Meng, Qingxue; Wu, Xueliang; Wang, Hao; Xue, Jun (Frontiers in Pharmacology, 2022)
Colon adenocarcinoma (COAD) patients are at relatively high risk of SARS-CoV-2 infection. However, there is a lack of medical strategies to treat COVID-19/COAD comorbidity. In this study, puerarin, a natural product, is a known antiviral, antitumor, and immunomodulatory effect. Therefore, we hypothesized that puerarin could be used to treat COVID-19/COAD patients. Based on network pharmacology and bioinformatics analysis, the potential targets and pharmacological mechanisms of puerarin in COVID-19/COAD were identified. By intersecting the identified therapeutic target genes of puerarin, COVID-19-related genes and COAD-related genes, 42 targets of puerarin that could potentially treat COVID-19/COAD comorbidity were obtained. By using the 42 potential targets to construct the protein-protein interaction (PPI) network, we obtained 5 core target genes, namely RELA, BCL2, JUN, FOS, and MAPK1. The results of bioinformatics analysis revealed that puerarin could be able to treat COVID-19 through apoptosis, antiviral, antioxidant, NF-κB, MAPK, IL-17, TNF, and HIF-1 signaling pathway. The present study found that puerarin has potential to treat COVID-19/COAD patients. Those targets can provide a clue for the treatment of COVID19/COAD comorbidity.